2011
DOI: 10.1590/s0100-29452011000300023
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins, pigment stability and antioxidant activity in jabuticaba [Myrciaria cauliflora (Mart.) O. Berg]

Abstract: Different solvents were evaluated for the extraction of jabuticaba anthocyanin pigments, identifying, quantifying and verifying the stability of the anthocyanins, as well as the conduction of three antioxidant activity assays and determination of the vitamin C levels. The maceration with ethanol acidified with HCl 1.5 mol L-1 (85:15) provides better pigment extraction and stability. The skin is anthocyanin rich, presenting 1.59 and 2.06 g 100 g-1 of dry matter in the Paulista and Sabará varieties, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 29 publications
(18 reference statements)
5
37
1
7
Order By: Relevance
“…However, some bioactive compounds were already described: anthocyanins, mainly cyanidin and delphinidin 3-glucoside; ellagitannins, ellagic acid, vitamin C, limonene, terpenes, dietary fibers and others (Leite-Legatti et al, 2012;Abe et al, 2012;Lima et al, 2011;. In our studies, 1 and 2% of FJP in diets increased systemic antioxidant status.…”
Section: Troductionsupporting
confidence: 49%
“…However, some bioactive compounds were already described: anthocyanins, mainly cyanidin and delphinidin 3-glucoside; ellagitannins, ellagic acid, vitamin C, limonene, terpenes, dietary fibers and others (Leite-Legatti et al, 2012;Abe et al, 2012;Lima et al, 2011;. In our studies, 1 and 2% of FJP in diets increased systemic antioxidant status.…”
Section: Troductionsupporting
confidence: 49%
“…It is possible to verify the presence of several other not identified peaks, but they are possibly other phenolic compounds. Lima et al (2011) identified the anthocyanic phenolics cyanidin 3-glucoside and delphinidin 3-glucoside, however using another extragent.…”
Section: Resultsmentioning
confidence: 99%
“…O. Berg) fruit skins are especially rich in phenolic compounds, up to 9.79 g 100 g -1 DM (Alves et al, 2013) and 11.99 g 100 g -1 DM (Lima et al, 2008) in Sabará genotype. Among the phenolic compounds found in jabuticabeira fruit skins, the anthocyanins cyanidin 3-glucoside and delphinidin 3-glucoside were identified (Lima et al, 2011). These skins, which represent up to 43% of the fruit (Lima et al, 2008), are considered residue and, when discarded, carry secondary metabolites of great value due to their potential applications as insecticides and/or agrochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Some natural pigments from vegetable sources, anthocyanins for example, have great potential as indicators in intelligent packaging systems. These flavonoids are widely spread in nature comprising the largest group of water-soluble plant pigments, and they have been isolated mainly from flowers and fruits (ALIBERT, 2009;BORDIGNON JUNIOR et al, 2009;FAVARO, 2008;GOUVÊA et al, 2012;LIMA, 2011;STRACK;WRAY, 1994). Color expression of anthocyanins is strongly influenced by its structure, pH, co-pigmentation, temperature, UV radiation, and presence of oxygen providing different colors that range from salmon-pink through red and violet to nearly black (FRANCIS, 1989;GONNET, 1998;MAZZA;BROUILLARD, 1990;TORSKANGERPOLL;ANDERSEN, 2005).…”
Section: Experimental Designmentioning
confidence: 99%